2016
DOI: 10.1021/jacs.6b01005
|View full text |Cite
|
Sign up to set email alerts
|

Metallo-Supramolecular Self-Assembly of a Multicomponent Ditrigon Based on Complementary Terpyridine Ligand Pairing

Abstract: Predesigned complementary complexation of two 2,2':6',2″-terpyridine-based ligands was established by installing 2,6-dimethoxyphenyl substituents at the terpyridyl 6,6″-positions, which provided ancillary ion-dipole interactions in the coordination process and extra π-stacking stabilization in the resultant heteroleptic complex. The high-fidelity self-recognition ligation afforded facile access to the quantitative self-assembly of multicomponent triangle [Cd6L(3)3L(4)3] and ditrigon [Cd15L(3)6L(5)3] (that is, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(55 citation statements)
references
References 92 publications
2
53
0
Order By: Relevance
“…Intriguingly, upon treatment of [Cd 9 L 7 3 L 8 3 ] with 9 equiv of Zn II ions at 50 °C for 2 h, both the 1 H NMR and ESI‐MS spectra (Figure d and Figures S41 and S42) suggested that the Cd II –Zn II transmetalation selectively took place at the inner homoleptic <tpy‐Cd II ‐tpy> connections within the preserved framework to afford the heterometallic Sierpiński triangle [Cd 6 Zn 3 L 7 3 L 8 3 ] with two types of labile tpy‐metal complexes. This result was consistent with our previous observation that a more labile homoleptic complex could be transformed into a heteroleptic complex in the presence of additional 6,6′′‐substituted tpy ligands and Cd II ions . Unlike the conventional stepwise strategy used to construct heterometallic supramolecules,, the multicomponent self‐assembly in tandem with the site‐selective transmetalation based on the subtle dynamic variation provides the new way to construct novel assemblies not accessible through either direct self‐assembly or a stepwise approach.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Intriguingly, upon treatment of [Cd 9 L 7 3 L 8 3 ] with 9 equiv of Zn II ions at 50 °C for 2 h, both the 1 H NMR and ESI‐MS spectra (Figure d and Figures S41 and S42) suggested that the Cd II –Zn II transmetalation selectively took place at the inner homoleptic <tpy‐Cd II ‐tpy> connections within the preserved framework to afford the heterometallic Sierpiński triangle [Cd 6 Zn 3 L 7 3 L 8 3 ] with two types of labile tpy‐metal complexes. This result was consistent with our previous observation that a more labile homoleptic complex could be transformed into a heteroleptic complex in the presence of additional 6,6′′‐substituted tpy ligands and Cd II ions . Unlike the conventional stepwise strategy used to construct heterometallic supramolecules,, the multicomponent self‐assembly in tandem with the site‐selective transmetalation based on the subtle dynamic variation provides the new way to construct novel assemblies not accessible through either direct self‐assembly or a stepwise approach.…”
Section: Resultssupporting
confidence: 90%
“…Moreover, the low solubility of tpy‐Ru III adducts and the lack of photoluminescence of [Ru(tpy) 2 ] 2+ complexes limited the architectural diversity and the potential application as photoactive materials, respectively. To overcome the difficulty, our group developed a dynamic complementary ligand pair (Scheme ) for facile construction of multicomponent self‐assemblies . With the aim of further extending the topological scope, herein, we design and synthesize three novel 6,6′′‐substituted tpy‐based ligands, namely, 120°‐bent bistpy L 1 , 60°‐bent bistpy L 7 , and tristpy L 11 , for the construction of various metallo‐supramolecular 2D and 3D structures through one‐pot multicomponent self‐assembly.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve more sophisticated supramolecular systems with higher efficiency, great efforts have been made on multicomponent self-assembly, such as social self-sorting to compose a series of heteroleptic coordination sites, 16e,18-20 subcomponent self-assembly based on reversible imine bond formation and metal–ligand coordination, 17f,g,21 template-driven synthesis of discrete supramolecules, 22,23 etc. These one-pot strategies rather than combining all building blocks in a presynthesized ligand dramatically reduced the barrier in ligand design and synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Unless otherwise noted, reagents and solvents were used as received from Fisher Scientific (Loughborough, UK) and Sigma-Aldrich (St. Louis, MO, USA) without further purification. 4 -(4-Hydroxyphenyl)-2,2 :6 ,2"-terpyridine (1) [43], 9-anthraceneboronic acid [44], tetrakis(triethylammonium) ethylenediaminetetraacetate (TEA-EDTA) [45], 2,5-dibromo-3-hexylthiophene [46], mono-brominated P3HT (Br-P3HT) [19], 6,6"-di(anthracen-9-yl)-4 -(4-methoxyphenyl)-2,2 :6 ,2"-terpyridine (L2) [19], 4 -(4-methoxyphenyl)-2,2 :6 ,2"-terpyridine (L3) [47], and (L2-Zn-L3) complex [48] were prepared according to the reported procedures.…”
Section: Methodsmentioning
confidence: 99%